Autoridad religiosa y autoridad política en "De haruspicum responso" de Cicerón - Cairo, María Emilia (2017)
The aim of this paper is to analyze the relationship between religious knowledge and belonging to the group of the boni cives, as formulated by cicero in his speech "De haruspicum responso". From our viewpoint, both when he rejects Clodius´ accusations and when he presents his own interpretation of the responsum, cicero poses a close correlation between knowledge about religio –how to behave according to mores maiorum, how to understand messages sent by the gods– and political auctoritas. By ascribing Clodius to the category of deteriores cives, due to the fact that he has violated every single religious norm, and that he conspires against harmony among the optimates, cicero excludes him from the group of boni cives. After a brief introduction that summarizes the reception of the speech and the context in which it was delivered, we present an analysis of the sourcesof religious authority and its connection to roman identity as presented in sections 18-19 of the speech. then, we turn to the definition of deteriores cives in order to observe how Cicero includes clodius under this designation. in the final section of the paper, some conclusions are advanced.